Evolution to decay of upwelling and associated biogeochemistry over the southeastern Arabian Sea shelf. Issue 1 (16th January 2016) - Gupta, G. V. M.; Sudheesh, V.; Sudharma, K. V.; Saravanane, N.; Dhanya, V.; Dhanya, K. R.; Lakshmi, G.; Sudhakar, M.; Naqvi, S. W. A.
Abstract: Observations along 10 shelf transects in 2012 near 10°N in the southeastern Arabian Sea revealed the usual warm oligotrophic conditions during the winter monsoon and upwelling of oxygen‐deficient, nutrient‐rich cool water during the summer monsoon (SM). By changing an oligotrophic to a nutrient‐replete condition, the upwelling is the major process that regulates the biogeochemistry of this shelf. Its onset is perceptible at 100 m depth between January and March. The upwelling reaches the surface layer in May and intensifies during June–July but withdraws completely and abruptly by October. Despite the nutrient injection, the primary production during SM, integrated for euphotic zone, is comparable to that during the preceding spring intermonsoon (SIM). Again, as usual, the high oxygen demand coupled with low concentration in the upwelled subsurface waters causes severe oxygen depletion below the shallow pycnocline. The oxygen concentrations/saturations of 2012 on the midshelf are similar from those of mid‐1958 to early 1960, except for marginally higher values during the peak upwelling period due to relatively weak upwelling in 2012. This implies little anthropogenic influence on coastal hypoxia unlike many other coastal regions. In 2012, the inner shelf system shifted from net autotrophy in SIM to net heterotrophy in SM but on an annual basis it was net autotrophic (gross primary production to community respiration ratio, GPP/ R :1.11 ± 0.84) as organic production exceeded consumption. Key Points: First modern time‐series‐coupled upwelling and biogeochemical study in the southeastern Arabian Sea The 2012 shelf oxygen levels are similar to 1958–1960 except marginal variation during peak upwelling Despite shifts in seasonal trophic status, the inner shelf system exhibited annual net autotrophy